Correction: 20.7% highly reproducible inverted planar perovskite solar cells with enhanced fill factor and eliminated hysteresis. Issue 5 (29th April 2019) - Liu, Xixia; Cheng, Yuanhang; Liu, Chao; Zhang, Tianxiang; Zhang, Nengduo; Zhang, Siwen; Chen, Jingshen; Xu, Qinghua; Ouyang, Jianyong; Gong, Hao
Abstract : Correction for '20.7% highly reproducible inverted planar perovskite solar cells with enhanced fill factor and eliminated hysteresis' by Xixia Liu et al., Energy Environ. Sci., 2019, DOI: ;10.1039/c9ee00872a .